Information Feedback Model for IoT Applications Based on of Basic Ability in Educational Practice of Preschool Education Major in Higher Vocational Education. (18th August 2022) - Wang, Ping; Xie, Wensi
Abstract : In order to solve the problem that the measurement of students' behavior preference is inaccurate and affects the teaching effect in the information feedback model of basic ability of educational practice, an information feedback model of basic ability of educational practice of preschool education major in higher vocational education is proposed. A feedback metacognitive intervention mechanism is designed from the perspective of learners to reflect learning performance from three aspects: cognitive results, behavior performance, and learning strategies. The focus index is introduced to extract the characteristics of classroom teaching information of professional education. Design a multisource education information fusion algorithm, fuse the ability information of the three dimensions of learning performance, and measure students' behavior preferences. Construct the information feedback model of practice basic ability, get the predicted information feedback score, and measure the teaching effect. The experimental test shows that the average score of this model is 8.97 points higher than the pretest, 5.05 points and 3.33 points higher than the model based on data mining and cluster analysis, respectively. Therefore, it can improve the teaching quality of preschool education.